Materialism is Not the Solution - Harman, Graham (The Nordic Journal of Aesthetics, 2016)
This article defends a new sense of “formalism” in philosophy and the arts, against recent materialist fashion. Form has three key opposite terms: matter, function, and content. First, I respond to Jane Bennett’s critique of object-oriented philosophy in favor of a unified matter-energy, showing that Bennett cannot reach the balanced standpoint she claims to obtain. Second, I show that the form/function dualism in architecture gives us two purely relational terms and thus cannot do justice to the topic of form. Third, I argue against Greenberg, Heidegger, and McLuhan that content cannot be trivialized in favor of deeper form. I close with a new conception of mimesis as performance rather than as the fabrication of copies. The form underlying any work’s content is provided by the spectator herself as the only real object that does not withdraw from the aesthetic scene.